The application mode and quality improvement of the integrated medical and nursing ward rounds (医护一体化查房应用模式与质量改进) - WANG Yali (王亚丽); WEI Yongchun (魏永春); E Haiyan (鄂海燕); DONG Yuxia (董玉霞); JIANG Jing (姜婧); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
The integrated medical and nursing ward rounds contributes greatly to quality improvement of clinical diagnosis and treatment, better meets the needs of patients, and promotes the harmonious development of the doctor-patient relationship. With the continuous development of modern medicine, medical science is becoming increasingly specialized, and increasing attention has being paid to the inter-professional cooperation. The implementation of medical and nursing integrated ward rounds is an important measure to promote medical and nursing cooperation. In order to promote the in-depth development, sustainability and standardization, this article briefly discussed the practice and quality improvement of the integrated medical and nursing ward rounds, and provided a reference basis for its clinical application. (医护一体化查房有助于提高临床诊疗的质量, 更好地满足患者的需求, 促进医患关系的和谐发展。随着现代医学的不断发展, 医学领域的专业化程度越来越高, 专业间合作的重要性逐渐受到重视。因此, 推行医护一体化查房是促进医护合作的重要措施。本文浅析医护一体化查房应用模式与质量改进, 旨在促进医护一体化查房的深入开展及持久性、规范性, 为医护一体化查房的应用提供参考依据。)